My imaginary Mary - Hand, Cynthia, 1978-; Ashton, Brodi; Meadows, Jodi (Mary, 2022)
When two masterminds--Mary, the daughter of Mary Wollstonecraft, and Ada, the daughter of Lord Byron--are brought together by fate, they make a shocking--and magical--discovery that draws the attention of a mad scientist.